Job Outcome: Job Involment, Job Characteristics Dan Work Engagement Sebagai Variabel Intervening - Muhammad Andi Prayogi; Muhammad Fahmi (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
This study aims to determine and analyze the model of performance achievement (job outcome) and variables that affect job outcomes including job involment, job characteristics and work engagement. The population in this study were private banking account officers in the city of Medan with a total sample of 385 Account officers. This study uses a Structural Equation Modeling Part Least Square (SEM PLS) model. The results of this study prove that Job Involment, Job Characteristics and Work Engagement have a significant influence on the Job Outcomes of Private Banking Account Officers in Medan City, then Job Involment and Job Characteristics ob Characteristics have an indirect effect on Job Outcome through Work Engagement as an intervening variable.